Pengaruh Model Ecirr Berbantuan Adobe Flash CS6 Terhadap Hasil Belajar IPAS Kelas V SD Negeri 064973 Bhayangkara T.A 2024/2025 - Yori Elizhia Saragih; Imelda Free Unita Manurung; Elvi Mailani; Fahrur Rozi; Suyit Ratno (Universitas Batanghari Jambi, 2026)
This study aims to determine the influence of the ECIRR model assisted by Adobe Flash CS6 on the learning outcomes of IPAS class V of SD Negeri 064973 Bhayangkara T.A 2024/2025. This type of research uses a quantitative approach with quasi-experimental. The research design used is a pretest-posttest control group design, where both groups will be given a pretest and posttest. The population of this study is the fifth grade of SD Negeri 064973 Bhayangkara, which consists of 44 students. The sample in this study came from all the populations used, namely 44 students. The data collection techniques in this study used observation, interviews, tests, and documentation. The test of this research instrument uses validity tests, reliability tests, difficulty levels, and differentiation tests. The data analysis technique in this study uses normality test, homogeneity test, and t test. The results of the study showed that the learning outcomes of students after using the ECIRR model assisted by Adobe Flash CS6 on the learning outcomes of IPAS class V of SD N064973 Bhayangkara especially in ecosystem materials were improved. This can be seen and proven from the average student learning outcomes in the pretest and posttest given. Where the students' pretest score with an average of 44.23 and an increase in the posttest score with an average of 72.68. That way, from testing the research hypothesis with a t-test with the provision of a posttest value at the sig level of 0.05 with the provision that if the tcount is > ttable, H0 is rejected and Ha is accepted and vice versa. The results of the analysis test in the t-test obtained a tcount of 4.278 while for ttable it was 1.681.